Explicit parity violation inSU(2)(L)circle times SU(2)(R)circle times U(1)(B-L) models - Diaz, Henry; Castillo-Ruiz, E.; Ravinez, O. Pereyra; Pleitez, V [UNESP] (Iop Publishing Ltd, 2021)
Here, we propose models with SU(2)(L) circle times SU(2)(R) circle times U(1)(B-L) electroweak gauge symmetry, in which parity (or charge conjugation) is explicitly broken and the interactions of left- and right-handed fermions are completely different from each other at any energy scale. In this type of model, there is no restoration of parity at high energies. However, as in all left-right symmetric models, the electroweak charged interactions of quarks and leptons appear to be only left-handed at low energies, because the right-handed interactions are suppressed by the masses of the respective charged vector bosons and/or because these interactions may be much weaker than the left-handed ones.
Keywords: left-right model; new vector bosons; parity violation